Assessment of the Association Between Cigarette Smoking and Cognitive Performance in Patients With Schizophrenia-Spectrum Disorders: A Case-Control Study - Stramecki, Filip; Kotowicz, Kamila D.; Piotrowski, Patryk; Frydecka, Dorota; Rymaszewska, Joanna; Beszłej, Jan Aleksander; Samochowiec, Jerzy; Jabłoński, Marcin; Wroński, Michał; Moustafa, Ahmed A.; Misiak, Błazej (Frontiers in Psychiatry, 2018)
The prevalence of cigarette smoking is significantly higher in patients with schizophrenia compared to the general population. Schizophrenia is also characterized by cognitive impairments that can be detected in the premorbid phase of illness. However, studies addressing the association between cigarette smoking and cognition in patients with psychosis have provided mixed findings. Therefore, the aim of this study was to assess the relationship between tobacco smoking and cognitive performance in patients with schizophrenia. In this case-control study, we recruited 67 inpatients with schizophrenia (34 cigarette smokers) and 62 healthy controls (30 cigarette smokers) at two clinical sites (Wroclaw and Szczecin, Poland). Cognitive performance was examined using the Repeatable Battery for the Assessment of Neuropsychological Status. Smoking dependence was determined using the Fagerström Test for Nicotine Dependence (FTND) and the pack-year index. Results show that, after adjustment for potential confounders, smokers with schizophrenia presented significantly lower scores on delayed memory tests compared to non-smokers with schizophrenia (F = 11.07, p = 0.002). In healthy controls, after adjustment for age, sex and education level, smokers had significantly lower scores in immediate memory (47.1 ± 6.4 vs. 52.0 ± 4.0, F = 11.64, p = 0.001), visuospatial/constructional functions (34.8 ± 3.8 vs. 37.7 ± 1.8, F = 12.86, p = 0.001) and global cognition (177.0 ± 15.7 vs. 191.2 ± 14.0, F = 12.63, p = 0.001) compared to non-smokers. There were no significant correlations between FTND scores or pack-year index and cognitive performance neither in patient nor control group. Our results show that cigarette smoking is related to worse delayed memory performance in schizophrenia patients as well as deficits of immediate memory, visuospatial/constructional functions and global cognition in controls. Longitudinal studies are required to establish causal interference between smoking and cognition in patients with schizophrenia.